Les réformes du marché du travail au Japon et en République de Corée: étude de cas comparée de l'élaboration des politiques dans les années 2000 - Yun, Ji-Whan (Revue internationale du Travail, 2011)
Dès la fin des années 1990, le Japon et la Corée ont entrepris des réformes du marché du travail souvent présentées comme un simple processus d'assouplissement. Partant, toutefois, de la perspective du «double mouvement» de Polanyi, l'auteur étudie la façon dont ces pays ont intensifié leur recours au marché tout en recherchant la stabilité sociale. Passant en revue les mesures législatives liées à la libéralisation de l'emploi et à la garantie de revenus, il analyse les différentes méthodes adoptées par ces deux pays pour réformer leur marché du travail. En conclusion, il avance que leurs voies de réformes divergentes tiennent à la spécificité des mécanismes utilisés pour élaborer leurs politiques ainsi qu'au contexte propre à chacun d'entre eux.
Political Science
Keywords: Corée R; Japan; Japon; commentaire; flexibilité du travail; politique du travail; protection sociale; segmentation du marché du travail; sécurité de l'emploi

Territoire, innovation et développement durable : l'émergence d'un nouveau régime conventionnel? - Buclet, Nicolas (Revue d'Économie Régionale & urbaine, 2011)
ENG TITLE: Territory, innovation and sustainable development: towards a new conventional regime? ABSTRACT: The paper examines the increasing number of diverse local development initiatives around the world aiming to break away from the predominant economic system. These initiatives, we argue, despite a somewhat visible disparity, largely rest on relatively similar principles, values and references. We argue that they are effectively laying the foundation for a new conventional regime more attuned to sustainable development goals. The paper analyses the characteristics of this regime, which refuses market dominance and favours reciprocal exchanges, as defined by Karl Polanyi. It is, nevertheless, necessary to question the potential and limitations of this conventional regime. (English)
Geography
Keywords: Territoire; conventions; development economics; développement durable; economic development; economics; environment; innovation; mathematical models; sustainable development; territory

Penser l’institution et le marché avec Karl Polanyi - Maucourant, Jérôme; Plociniczak, Sébastien (Revue de la régulation. Capitalisme, institutions, pouvoirs, 2011)
Bien que Karl Polanyi (1886-1964) n’ait jamais eu pour ambition « d’élaborer une théorie complète des institutions économiques », ce texte met en évidence qu’il y a, dans son œuvre, une analyse aussi implicite que profonde du marché appréhendé comme institution ou « processus institutionnalisé ». À l’encontre de la croyance économique conventionnelle, l’œuvre de Polanyi permet de comprendre que le marché, n’est ni spontané ni autorégulateur. Plus encore, à suivre Polanyi, le capitalisme ou « société de marché » se caractérise par un fait culturel spécifique : la croyance utopique en l’autorégulation marchande. Une origine de la crise économique actuelle peut ainsi être mise en évidence. Plus généralement, tout économiste contemporain soucieux des problématiques de l’institution et du marché peut, avec Polanyi, resituer de façon novatrice les marchés au sein des contextes socio-historiques dans lesquels ils se déploient. ENG translation: Although Karl Polanyi (1886-1964) never had the ambition "to elaborate a complete theory of economic institutions", this text emphasizes that there is in his work an analysis both implicit and profound Market as an institution or "institutionalized process". Contrary to conventional economic belief, Polanyi's work makes it possible to understand that the market is neither spontaneous nor self-regulating. Moreover, to follow Polanyi, capitalism or "market society" is characterized by a specific cultural fact: the utopian belief in mercantile self-regulation. An origin of the current economic crisis can thus be highlighted. More generally, any contemporary economist concerned with the problems of the institution and the market can, with Polanyi, innovatively place markets in the socio-historical contexts in which they unfold.
Economics
Keywords: capitalisme; crise; encastrement; institution; marché autorégulateur; marchés; société de marché; utopie

Les sciences sociales africanistes à l’épreuve des projets de développement. Peuvent-elles dépasser l’opposition entre l’universalisme de l’économie et le relativisme de l’anthropologie ? - Hugon, Philippe (Cahiers d’études africaines, 2011)
RésuméLes disciplines économiques et anthropologiques, notamment africanistes, ont été généralement caractérisées par des exclusions et des cloisonnements. L’économie s’intéresse principalement aux sociétés marchandes et capitalistes occidentales et mobilise des catégories à vocation universelle alors que l’ethnologie ou l’anthropologie prennent pour champ les sociétés « primitives » exotiques ou premières, et privilégient les catégories et représentations des acteurs. Le champ du développement a été un lieu de rencontre obligé des deux disciplines. L’économie a cherché à aborder les sociétés non occidentales et l’anthropologie a été confrontée aux projets de développement. Cet article rappelle les oppositions historiques entre les éclairages économiques et anthropologiques avant de présenter certains enjeux méthodologiques et épistémologiques d’une anthropologie économique du développement en l’illustrant par la filière coton., Abstract ENG: Economics and anthropology as africanist social sciences have known a separate evolution. Economics are mainly interested by capitalism and Western societies and mobilize universalist concepts. Ethnology or anthropology on the other hand study more traditional, “primitive” or exotic societies. Howewer the two meet and have some confrontation when they study development. Firstly, this article recalls the historical oppositions between the economical and the anthropological points of view. Secondly, it presents some of the methodological and epistemological stakes of development economic anthropology. Lastly this paper illustrates this debate in examining the case of the chain value within the economic overall process of coton production and exchange.
Economics; African Studies
Keywords: africanist social science; cotton production; exchange

Le concept de « marchandise fictive », pierre angulaire de l'institutionnalisme de Karl Polanyi ? - Postel, Nicolas; Sobel, Richard (Revue de philosophie économique, 2011)
The notion of “fictitious commodities” is not simply a convenient heterodox slogan to criticize the radical limits of any trade system and the analytical limits of the dominant theory. It is rather the foundation of the institutional perspectives that underlie all Karl Polanyi’s sociohistoric analyses. This article explains and articulates both the theoretical level using the institutional approach to commodities and a philosophical level using a broad definition of the economy. There is, however, a limit to the notion of the institution, which connects both levels: it is not articulated practically such that the potential and critique of this construct may be weakened.
Sociology; Economics
Keywords: capitalisme; institution; marchandises fictives; raison pratique; économie substantive

Y a-t-il une économie sartrienne ? - Kail, Michel; Sobel, Richard (L'Homme & la société, 2011)
RésuméEn dépit de l’absence d’un exposé économique systématique dans l’œuvre de Sartre, nous soutenons qu’il y a bien une économie sartrienne, même si celle-ci est encore à développer. Le statut que Sartre réserve à la « rareté » lui permet de faire un pas supplémentaire vers la critique de l’économisme par rapport à celui déjà effectué par Karl Polanyi, qui s’est contenté de récuser la confusion entretenue entre l’économique et sa définition formelle. La rareté, nous enseigne Sartre, ne saurait en effet être soumise au traitement de la raison instrumentale, mais considérée, ajoute-t-il, comme un fait humain dans l’histoire. Aussi, l’analyse économique ne doit-elle pas s’appuyer sur la notion de « nature » et la thématique de l’homme confronté à la nature, en l’occurrence « ingrate », mais articulée sur la notion de « monde » telle que la philosophie sartrienne l’élabore., Despite the absence of a systematic analysis of economics in Sartre’s work, we argue that there can indeed be said to be a Sartrean economics, even if it is one that still awaits development. The status which Sartre accords to the concept of Scarcity allows him to advance the critique of economism begun by Karl Polanyi, who, for his part, had been satisfied simply to challenge the reduction of economics to its formal definition. Scarcity, Sartre teaches us, should not be submitted to the process of instrumental reason, but considered as a fact of human history. Economic analysis, meanwhile, should not be based solely on the theme of man’s confrontation with a typically ungrateful Nature, but articulated through the concept of World as elaborated in Sartrean philosophy.
Political Science; Philosophy
Keywords: SARTRE; Jean-Paul; 1905-1980; economic systems

Avez-vous lu Polanyi ? - Maucourant, Jérôme (HAL, 2011)
"Cette étude présente le parcours intellectuel de Karl Polanyi (1886-1964), à la croisée de l'économie, de l'histoire et de la sociologie, et propose une synthèse de l'ensemble de son oeuvre." Postface accessible en ligne : [ http://www.contretemps.eu/lectures/bonnes-feuilles-avez-vous-lu-polanyi-j%C3%A9r%C3%B4me-maucourant-postface ]
Economics; Sociology
Keywords: Great Transformation; The (Book); La Grande Transformation; critique and interpretation; critique et interprétation; libéralisme; économie politique

À propos de « ceux qui sont en dehors de la société ». L'indigent et l'assistance publique au Québec dans la première moitié du XXe siècle - Petitclerc, Martin (Revue d'histoire de L'Amerique francaise. automne2011/hiver2012, Vol. 65 Issue 2/3, p227-256. 30p., 2011)
The “ Loi établissant le service de l'assistance publique" (Public Welfare Act) sparked considerable controversy after its adoption in 1921 .The Act provided for provincial and municipal grants to private and religious institutions providing shelter to the poor and destitute. Led by Henri Bourassa, among others, the debate concerned the problem of state intervention in an area traditionally conceived of as the responsibility of the Church. In contradiction to Bourassa's theories, most historians analyzed the A c t through the rubric o f modernization as a necessary affirmation of State prerogatives in the area of social protection. In this article, we argue that this Act is an attempt (largely successful) to consolidate a form of liberal governmentality based on, since the 19th century, what Karl Polanyi termed “the figure of the pauper" According to this perspective, the 1921 A c t is not a significant stage in the age-old struggle between Church and State, but rather a time of reform in liberal politics in regards to "the indigent 'The latter leggally defined as unable to work and without family support, and therefore “ outside of society," an expression of the day, allowed justifying the development o f a private/public system of charitable assistance against the project o f social policies founded on a universal conception of social rights. The article presents this dynamic through an analysis of the contentious issue of the rights of indigents to public assistance. (English)
History
Keywords: BOURASSA; Henri; 1868-1952; Canada; Quebec; church & state - Canada; liberalism - Canada; poor people - Canada; poor people - government policy; poor people - services for - history; public welfare - Canada - history

Polanyi contre Freeman. (Polanyi against Freeman. With English summary.) - Postel, Nicolas; Sobel, Richard (Revue de la Regulation, 2011)
The dominant approach of CSR is based on the concept of "stakeholders" (R. E. Freeman). More than a theory, it is a slogan which irrigates as much the scientific discourse as the manager and political discourses. We can make two readings of this slogan. The first one, which is very reducing for us, consists on the deconstruction of the firm as institution and its replacement by a market representation based on bilateral exchanges between rational individuals. The second one, more promising in order to identify the potentialities of CSR in terms of regulation, intends to found the notion of stakeholder on a theory of actor and institution. It is the position which we defend by mobilizing Karl Polanyi's institutionalism.
Sociology; Economics
Keywords: Marxian; Sraffian; business objectives of the firm; corporate culture; current heterodox approaches: institutional; current heterodox approaches: socialist; diversity; evolutionary; social responsibility